Effect of pulsed laser irradiation on the SiC surface. Issue 3 (2nd February 2017) - Suess, Manuela; Wilhelmi, Christian; Salvo, Milena; Casalegno, Valentina; Tatarko, Peter; Funke, Matthias
Abstract: The effect of a pulsed laser irradiation (Nd:YVO4, 1064 nm) in air on the surface morphology and chemical composition of silicon carbide and on the adhesion with an epoxy adhesive was investigated. Scanning and transmission electron microscopies, atomic force microscopy, and X‐ray photoelectron spectroscopy revealed that the laser treatment reduced the contamination level of the surface and induced the formation of a silica‐based nanostructured columnar layer on the SiC surface. The mechanism for the formation of five different microstructural regions is described in this paper. In addition, the formation of a 5‐10‐nm‐thick graphite layer between the oxide layer and SiC was observed. The joining test with Hysol ® EA9321 showed that the nanostructured columnar silica layer was completely infiltrated by the adhesive, thus leading to a significant increase in the joined specific area and a mechanical interlocking at the adhesive/substrate interface. Nevertheless, the apparent shear strength of the joined SiC samples slightly decreased after the laser processing of the surfaces from about 42 MPa for lapped SiC to about 35 MPa for laser‐nanostructured SiC. The formation of the graphite layer was found to be responsible of the poor adhesion properties of the SiC surfaces modified by the laser radiation.